Die varietät der aussprachenorm - Petrenko, A.D.; Petrenko, D.A. (Культура народов Причерноморья, 2013)
The development of theory and history of literary languages, the problems of Dialectology, Areal Linguistics proved that the language reality and the forms of its functioning are rather diverse. The achievements of Linguistics made it possible to realise deeper the polysystematic character of any national language, which by itself presents a complicated, hierarchily organised macrosystem, formed historically and uniting different forms of existance. The notion of the objective language norm is correlated with such notions as system and structure of the language. In modern Linguistics the accepted approach regards language as the system of conventional means, and speech as one of the formes of system existance. If language and system are being apposed, it leads to separation of system and norm. The phenomenon was most consistently defined in the works of linguists in the XXth century. They mainly agreed on the following: norm exists in the language itslf; in a definite way it is connected with the system; is defined by the system as sum of opportunities, which exist in a definite language, namely, as the system of models which have not been realized. Language bearers do not realise either what norm is, or what phonological oppositions, existing within the frames of norm, are. These deviations may be the result of the fact that a bearer of a language speaks a certain dialogue; it may depend on his/her educational level, social and professional communication environment and, besides, generation characteristic features. Different forms of communication are used according to the situation. Among them only the literary form is a universal one, as it does not depend on the area and is impersonal by its character. Key words: pronunciation norm; Sociolinguistics; Sociophonetics; an unstable rule; phonological variability.